L'economia della conoscenza: innovazione, produttività e crescita economica nei secoli XIII-XVIII / The knowledge economy: innovation, productivity and economic growth, 13th to 18th century - Nigro, Giampiero (Datini Studies in Economic History, 2023)
The studies presented here analyze the relationship between the knowledge economy and innovations, productivity, and economic growth in the premodern period (13th-18th centuries) by considering the following questions: how was "useful knowledge" transmitted between individuals, across space, and across generations? How could commercial and industrial productivity have been associated with the expansion of such knowledge? When and where was useful knowledge concentrated in such a way that a relatively large number of innovations and inventions could cause revolutionary breakthroughs in particular sectors of the economy?